VD_FINDINFO Décision / 2019 / 443 vom 29. April 2019 - VD Tribunal cantonal (2019)
REJET DE LA DEMANDE, DÉFENSE D'OFFICE, CAS BÉNIN | 130 let. c CPP (CH), 132 al. 1 let. b CPP (CH), 393 al. 1 let. a CPP (CH)